Evaluation of MoS2 Films Fabricated by Metal-Organic Chemical Vapor Deposition Using a Novel Mo Precursor i-Pr2DADMo(CO)3 Under Various Deposition Conditions. (2020) - Yamazaki, K.; Hibino, Y.; Oyanagi, Y.; Hashimoto, Y.; Sawamoto, N.; Machida, H.; Ishikawa, M.; Sudo, H.; Wakabayashi, H.; Ogura, A.
ABSTRACT: Molybdenum disulfide (MoS2 ) is expected to be applied for devices in various fields owing to its unique characteristics. Establishing a high-productivity manufacturing method which yields high quality films is an important and unresolved issue for the practical applications of MoS2 . Among different techniques conducted by researchers all over the world, our approach is cold-wall metal-organic chemical vapor deposition, and we previously reported the deposition of MoS2 with i-Pr2 DADMo(CO)3, a novel Mo precursor [S. Ishihara, et al., MRS Advances 3, 379-384 (2018).]. In this study, with the aim of further improving the quality of the MoS2 film using this new Mo precursor, various film formation conditions were controlled and the influence on the film quality was investigated. X-ray photoelectron spectroscopy, atomic force microscopy and Raman spectroscopy were used as evaluation techniques of the samples. As a result, mm-scale uniform film was formed with the deposition time less than 30 min. at temperature as low as 400 °C to 500 °C. It was revealed that maintaining low Mo/S supply ratio (SRMo/S ) is crucial in fabricating high quality films.